2020
DOI: 10.1101/2020.07.23.216408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Mast Cell Phenotypes in Benign versus Cancer Tissues and Prostate Cancer Oncologic Outcomes

Abstract: We previously reported that high numbers of mast cells in benign (extra-tumoral) regions of the prostate are associated with worse outcomes after radical prostatectomy including biochemical recurrence and the development of metastases. Herein, on a cohort of 384 men, we performed mast cell subtyping and report that higher minimum number of the tryptase-only (MCT) subset of extra-tumoral mast cells is associated with increased risk of biochemical recurrence (comparing highest to lowest tertiles: HR 2.20, 95% CI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Mast cells are one of the important innate immune cells in the immune system (33). Many studies have shown that low levels of mast cells were associated with poor survival and advanced tumors (34)(35)(36). Fortunately, we discovered that the activity of NK cells remained low in subtype A and low CRG_score group; however, the activity of mast cells was high.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are one of the important innate immune cells in the immune system (33). Many studies have shown that low levels of mast cells were associated with poor survival and advanced tumors (34)(35)(36). Fortunately, we discovered that the activity of NK cells remained low in subtype A and low CRG_score group; however, the activity of mast cells was high.…”
Section: Discussionmentioning
confidence: 99%